2015
DOI: 10.1007/s10265-015-0740-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and biochemical characterization of isoprene synthases from the tropical trees Ficus virgata, Ficus septica, and Casuarina equisetifolia

Abstract: Three isoprene synthase (IspS) cDNA clones have been isolated from tropical trees (Ficus septica, F. virgata, and Casuarina equisetifolia), and their enzyme properties have been compared with those of Populus alba IspS. Phylogenetic analysis of the deduced amino acid sequences with known monoterpene synthase resolved IspS from F. septica and F. virgata and other IspSs in a clade together with TPS-b clade I, whereas IspS from C. equisetifolia was within another clade, sister to TPS-b clade II. The optimum react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…This was somewhat surprising, since the gene expression data using fluorescence reporter showed that the increase in strength of RBS translated to higher yields of protein. The observed limitation in the isoprene production can be explained by several lines of reasoning: (i) if the overproduction of isoprene synthase is toxic, cells can potentially reduce this effect by either turning down expression or increasing degradation of IspS protein; (ii) due to the inherently high K m of IspS, the reduced availability of substrate can become a limiting factor in the biosynthesis of isoprene ( 49 , 59 ); (iii) since isoprene synthase competes with geranyl pyrophosphate synthase and farnesyl pyrophosphate synthase for DMAPP, the overexpression of IspS can cause a depletion of prenyl phosphates (e.g., undecaprenyl phosphate) required for biosynthesis of various cell wall polymers ( 60 ); (iv) as it has been previously reported that isoprene synthase forms inclusion bodies when overexpressed ( 49 ), protein aggregation can inhibit the enzymatic activity of IspS.…”
Section: Discussionmentioning
confidence: 99%
“…This was somewhat surprising, since the gene expression data using fluorescence reporter showed that the increase in strength of RBS translated to higher yields of protein. The observed limitation in the isoprene production can be explained by several lines of reasoning: (i) if the overproduction of isoprene synthase is toxic, cells can potentially reduce this effect by either turning down expression or increasing degradation of IspS protein; (ii) due to the inherently high K m of IspS, the reduced availability of substrate can become a limiting factor in the biosynthesis of isoprene ( 49 , 59 ); (iii) since isoprene synthase competes with geranyl pyrophosphate synthase and farnesyl pyrophosphate synthase for DMAPP, the overexpression of IspS can cause a depletion of prenyl phosphates (e.g., undecaprenyl phosphate) required for biosynthesis of various cell wall polymers ( 60 ); (iv) as it has been previously reported that isoprene synthase forms inclusion bodies when overexpressed ( 49 ), protein aggregation can inhibit the enzymatic activity of IspS.…”
Section: Discussionmentioning
confidence: 99%
“…Two specific reverse primers (FsIspS‐pro1 and FsIspS‐pro2) were designed close to the 5′‐end of the FsIspS coding region (Oku et al . ). Sequences of primers used in this study are found in Supporting Information Table S3.…”
Section: Methodsmentioning
confidence: 97%
“…Briefly, genomic DNA was digested with four blunt-end restriction enzymes (Dra 1, Eco RV, Pvu 11 and Stu 1) to yield four libraries that were then ligated to the GenomeWalker adaptor. Two specific reverse primers (FsIspS-pro1 and FsIspS-pro2) were designed close to the 5′-end of the FsIspS coding region (Oku et al 2015). Sequences of primers used in this study are found in Supporting Information Table S3.…”
Section: Isolation Of F Septica Isps (Fsisps) Gene Promotermentioning
confidence: 99%
“…Sequences of the gene(s) encoding for isoprene synthase (IspS) and/or the isoprene synthase protein have been isolated from a variety of emitter species. These include poplars ( Populus alba , Populus × canescens , Populus tremuloides , Populus trichocarpa , Populus nigra ) [ 93 , 94 , 95 , 96 ], kudzu ( Pueraria montana ) [ 95 ], willow ( Salix glabra ) [Accession JQ943918.1], figs ( Ficus virgata , Ficus septica ), the Australian pine tree ( Casuarina equisetifolia ) [ 97 ], black locust ( Robinia pseudoacacia ), Wisteria sp. [ 63 ], and most recently Arundo donax , a herbaceous species [ 98 ].…”
Section: Discussionmentioning
confidence: 99%